High-Tyrosol/Hydroxytyrosol Extra Virgin Olive Oil Enhances Antioxidant Activity in Elderly Post-Myocardial Infarction Patients - Mojgan Morvaridzadeh; Mehdi Alami; Nada Zoubdane; Hawa Sidibé; Hicham Berrougui; Tamàs Fülöp; Michel Nguyen; Abdelouahed Khalil (Antioxidants)
Cardiovascular disease (CVD), particularly atherosclerotic cardiovascular disease (ASCVD), is the leading cause of death worldwide, driven by factors like oxidative stress, inflammation, and lipid metabolism disorders. Although phenolic compounds such as Tyrosol (Tyr) and Hydroxytyrosol (HTyr) found in extra virgin olive oil (EVOO) have shown promising antioxidant and anti-inflammatory effects, their specific roles in modulating oxidative stress biomarkers and high-density lipoprotein (HDL) functionality in elderly populations, especially in those with prior myocardial infarction, are not fully understood. This study aimed to investigate the effects of EVOO phenolic compounds on oxidative stress biomarkers and HDL functionality, and related metabolic outcomes in both healthy and post-myocardial infarction (post-MI) elderly individuals. This pilot randomized clinical trial study included healthy and post-MI participants aged 65–85 years. Participants in each group were randomly assigned to consume 25 mL per day of one of three types of olive oils: high phenolic (HTyr/Tyr) extra virgin olive oil (HP-EVOO), extra virgin olive oil (EVOO), or refined olive oil (ROO) for a period of 26 weeks. Blood samples were collected at baseline and post-intervention to assess key biomarkers. Plasma levels of (poly)phenols, malondialdehyde (MDA), total antioxidant capacity (FRAP), lecithin-cholesterol acyltransferase activity (LCAT), and serum paraoxonase-1 (PON-1) activity were measured. A total of 34 individuals completed the study (mean age: 74 years). Baseline characteristics, including sex, age, body mass index (BMI), weight, blood pressure, and inflammatory markers like C-reactive protein (CRP) levels, did not differ significantly between the two groups. A significant increase in both FRAP levels and PON-1 activity was observed in post-MI participants following HP-EVOO consumption compared to baseline (p = 0.014). No significant changes were observed in MDA levels, LCAT activity, or plasma (poly)phenols. These results indicate that HP-EVOO may enhance antioxidant capacity, particularly FRAP and PON-1 activity, in elderly post-MI individuals. The observed differences between groups suggest that underlying cardiometabolic status may influence the response to olive oil phenolic compounds. Further studies are needed to explore the long-term cardiovascular effects.